Pengembangan instrumen penilaian self-regulated learning untuk peserta didik sekolah dasar - Ristyananda Putri Purnamasari; Supianto Supianto (Universitas Sebelas Maret, 2026)
This study aims to analyze the self-regulated learning (SRL) capabilities of elementary school students. Involving 317 students from grades 4, 5, and 6 in Sukoharjo, a questionnaire instrument was developed to measure metacognition, motivation, and learning behavior. The results showed that 43% of students were in the good category, 14% very good, 25% sufficient, and 18% poor. Learning motivation emerged as the strongest factor, with an achievement level of 85%. This research provides insights for educators to facilitate the development of students' SRL.